2012
DOI: 10.1108/03090561211189284
|View full text |Cite
|
Sign up to set email alerts
|

Unmasking the ambushers: conceptual framework and empirical evidence

Abstract: PurposeSport events organizers have recently undertaken to disclose to the general public instances where firms have conspired to ambush the official sponsors. In doing so, they have sought to sensitise audiences to sponsors' valuable contribution. However, what is the effect of such disclosure on ambush marketers' brands? This study aims to answer this question, using an experimental approach.Design/methodology/approachTwo successive experiments were conducted. The first study used a student sample (n=120) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 67 publications
1
33
0
Order By: Relevance
“…For example, Dunn and Schweitzer () in a study on trust and emotions conduct three different field experiments using adults waiting at a train station. Similarly, Mazodier et al () use trained assistants to conduct intercept interviews at public places such as parks and marketplaces. As Henry () points out, energetic research assistants with clearly visible university affiliation are good candidates who can help to easily approach and collect data from adults at these waiting spots.…”
Section: Best Practices In Sample Selectionmentioning
confidence: 99%
“…For example, Dunn and Schweitzer () in a study on trust and emotions conduct three different field experiments using adults waiting at a train station. Similarly, Mazodier et al () use trained assistants to conduct intercept interviews at public places such as parks and marketplaces. As Henry () points out, energetic research assistants with clearly visible university affiliation are good candidates who can help to easily approach and collect data from adults at these waiting spots.…”
Section: Best Practices In Sample Selectionmentioning
confidence: 99%
“…Consumers do not have strong negative feelings toward ambush marketing and seem to be indifferent to this practice (Shani & Sandler, ). Preliminary results show that the detection of ambush marketing does not appear to harm attitudes toward ambushing brands, unless consumers are briefed that ambush marketing harms the sports event (Mazodier, Quester, & Chandon, ; Wolfsteiner, Grohs, & Reisinger, ). Further research is necessary to fully understand consumer reactions to companies identified as sponsors as opposed to companies identified as ambushers.…”
Section: Limitations and Further Researchmentioning
confidence: 98%
“…Thus, a sponsor establishes a direct relational link with the event and is allowed to officially announce and communicate its sponsorship. In contrast, ambushers only establish an indirect link with the event through associations that express the ambushers’ (indirect) role within the event context (Grohs & Wolfsteiner, ; Meenaghan, ) and through the product category the sponsor and the ambusher share (Mazodier, Quester, & Chandon, ).…”
Section: Review Of Ambush Marketing Studies and Research Questionsmentioning
confidence: 99%
See 1 more Smart Citation
“…The ambush marketer operates in the media context of an event (e.g., on television or radio) and pays a rights fee to the broadcast company but not to the event (Crompton, 2004). Program sponsoring may result in several com panies in different countries presenting the same event to spectators (Mazodier et al, 2012). Evidence for suc cessful program sponsoring is manifold.…”
Section: Program Sponsoringmentioning
confidence: 98%